PENGARUH FAKTOR JOB DEMAND TERHADAP KINERJA DENGAN BURNOUT SEBAGAI VARIABEL MODERATING PADA KARYAWAN BAGIAN PRODUKSI PT.TRIPILAR BETONMAS SALATIGA - Putra, Yanuar Surya (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2010)
Every Organization and company will always work hard to increase employee performance to achieve organization goals that have been set. In other words the succeed of an organization depends on employee’s performance, the more efficient and effective employee’s performance will make organization goals more achieveble. There are various variables that influence employee’s performance. Some of those variables are job demand. Job demand describe the portion or “burden” that have to be carried or finish by the employee and sometimes also drive a psychological stressor toward employee. This research is try to measure how strong job demand influence employee’s performance and using burnout as moderating variable. Burnout can be defined as the highest level of stress that can cause illnes wheter is physically or mentaly. The object of this research is employee in production departement PT. Tripilar Betonmas Salatiga, and the result show that job demand is having a significant influence towards employee’s performance by using burnout as moderating variables. Keywords : Job Demand, Burnout, Employee’s performance